How to Improve The Quality of Accounting Information Systems from Organizational Perspective (Empirical Evidence from Banking Sector in Bandung – Indonesia) - Elza Fransisca; Yenni Carolina; Rapina (Conference Series, 2020)
Organizational structure and organizational commitment are the elements in the organization as well as the factors that support success in the application of AIS. Indonesian company phenomenon reveals that the Quality of AIS hasn't been properly applied in Indonesian banks. The aim of the research is to (1) study the impact of organizational structure and organizational commitment on the Quality of Accounting Information System (2) to look at the impact of the Quality of AIS on the quality of accounting information. This examination makes use of a survey methodology. Information gathering on this exam used questionnaires on 62 banking staff in Indonesia. The info that has been collected is processed utilizing SEM PLS. The outcomes of this examination is organizational structure and organizational commitment have an impact on the quality of accounting information and the quality of the AIS has a positive effect on the quality of accounting information.